STUDI KELAYAKAN FINANSIAL USAHA PUDING LAMOTA: PENDEKATAN NET PRESENT VALUE DAN INTERNAL RATE OF RETURN - Elsa Rahmawati; Elliza Rizki Wandani; Hasdita Elies Ramadani; Elisa Juniarti; Mia Maelani (Pusat Riset dan Publikasi, 2022)
Business or business feasibility studies are very suitable for various business categories including UMKM. Business or business feasibility studies have a very large role for the success and sustainability of micro, small and medium enterprises (UMKM). The profitable business scale resulting from business feasibility will have an impact on making the necessary policies or business strategies so that it will have an impact on the sustainability of the UMKM business. The Lamota Pudding Business is one of the UMKM that is engaged in by students of the Faculty of Economics and Management, Samawa University, Sumbawa Besar. As a new business, it is important to carry out a feasibility analysis of the business so that there is an overview of the sustainability of the business in the future. One aspect of feasibility in an economic perspective includes Net Present Value (NPV) and Internal Rate of Return (IRR). The results of the analysis show that the NPV of the Lamota Pudding business is Rp.41,916,566, - is positive or greater than zero so that it can be concluded that the Lamota Pudding business is feasible to continue. Meanwhile, the results of the IRR calculation for the Lamota Pudding business obtained an IRR of 200.45% greater than the generally accepted bank interest rate (12%) so that it can be concluded that the Lamota Pudding business is feasible to continue.